Effect of Pre-treatment on The Impregnation of Osmotically Dehydrated Fruits: A Review: Pre-treatment effect for impregnating osmotically dehydrated fruits - ASMAN, SALIZA; RAJA, SHALINI (Borneo Journal of Resource Science and Technology, 2023)
Osmotic dehydration is one of the alternative methods that is most frequently employed in the food industry to prevent large accumulation of food waste and postharvest losses, although it has a devastating influence on the textural and structural properties of the fruits. Considering that, this review offers innovative ideas and views on the impact of calcium salts, specifically calcium chloride and calcium lactate, on the impregnation of osmotically dehydrated fruits, along with various pre-treatments. Calcium chloride and calcium lactate salts assist in conserving the quality of fruits in the sense of colour, sensory, textural, structural, and other characteristics since some fruits are very perishable and rapidly degrade. Additional data showed that pre-treatments like blanching, freezing, drying, and ultrasound negatively affect calcium salt impregnation on fruit samples. The focus of this review is mainly on the preservation method of impregnating osmotically dehydrated fruits with calcium chloride and calcium lactate salt treatments, as well as blanching, freezing, drying, and ultrasound pre-treatments.